Pengaruh Live Music, Varian Menu Dan Atmosfer Terhadap Kepuasan Pengunjung Cafe Amstirdam Di Jl. Soekarno Hatta Kota Malang - Moh Andy Pamungkas; Nur Hidayati; Restu Millaningtyas (UNIVERSITAS ISLAM MALANG, 2026)
Abstract Coffee-based culinary delights have a unique appeal in Indonesia. The purpose of this study was to analyze the influence of live music, menu variety, and atmosphere on customer satisfaction at Cafe Amsterdam in Malang City. The location of this study was Amstirdam Coffee. Amstirdam Coffee itself has four branches in Malang City, one of which is Amstirdam Suhat, located at Ruko Soekarno Hatta Indah, No. D18, Jl. Mojolangu, Lowokwaru District, Malang City, East Java. The study used an explanatory method. The visitor population at Cafe Amsterdam in Malang City used the Hair formula to determine a sample of 95 consumers. The results of the study simultaneously examined the variables of Live Music, Menu Variety, and Atmosphere on Customer Satisfaction at Cafe Amsterdam in Malang City. Partially, Live Music, Menu Variety, and Atmosphere have a significant positive effect on customer satisfaction at Cafe Amsterdam, which is able to adapt to customer preferences. Keywords: Live Music, Menu Variety, Atmosphere, Customer Satisfaction